A brief telephone-delivered peer intervention to encourage enrollment in medication for opioid use disorder in individuals surviving an opioid overdose: Results from a randomized pilot trial. (1st November 2020) - Winhusen, Theresa; Wilder, Christine; Kropp, Frankie; Theobald, Jeff; Lyons, Michael S.; Lewis, Daniel
Highlights: Pilot trial of phone-delivered peer intervention for opioid overdose (OOD) survivors. Peer interventionists were in medication for opioid use disorder (MOUD) treatment. Twelve-month trial outcomes included MOUD enrollment, OOD recurrence, and opioid use. Our randomized pilot trial data are suggestive of beneficial intervention effects. Further development and testing of this peer intervention may be warranted. Abstract: Background: Medication for opioid use disorder (MOUD) can decrease the risk of opioid overdose (OOD) in individuals with opioid use disorder. Peer recovery support services (PRSS) are increasingly used to promote MOUD engagement but evidence of their efficacy is limited. This study's objective was to evaluate a single 20-minute telephone-delivered PRSS intervention for increasing MOUD enrollment and decreasing recurring OODs. Method: This single-site, randomized controlled pilot trial enrolled adults, primarily recruited from a syringe service program, with an opioid-positive urine drug screen (UDS) reporting having been treated for an OOD within the past 6 months. Participants (N = 80) were randomized to PRSS (n = 40) or Control (n = 40) condition with all participants receiving personally-tailored OOD education and naloxone. Outcome measures obtained at 3 (n = 66), 6 (n = 58), and 12 (n = 44) months post-randomization included verified MOUD enrollment (primary), self-reported OOD, and opioid use assessed by self-report and UDS. Results: Through 12-month follow-up, 32.5 % of PRSS, compared to 17.5 % of Control participants enrolled in MOUD (X 2 = 2.4, p = 0.12; odds ratio = 2.27 (0.79–6.49)). PRSS participants were significantly less likely to have experienced an OOD through 12-month follow-up (12.5 % of PRSS participants, 32.5 % of Control, p = 0.03). No significant treatment effect was found for opioid use through 12-month follow-up as measured by either opioid-positive UDSs or self-reported past month opioid use days. Based on self-report, PRSS had good acceptability for both the interventionists and participants. Conclusions: The results suggest that further development and testing of this PRSS telephone intervention to encourage MOUD enrollment and reduce OOD may be warranted.